PENGARUH PENERAPAN PENDEKATAN PEMBELAJARAN DEEP LEARNING TERHADAP KREATIVITAS SISWA PADA MATA PELAJARAN GEOGRAFI DI SMAN 10 MUARO JAMBI - Shita Utari; Ernawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the effect of implementing the Deep Learning approach on students’ creativity in Geography subjects at SMAN 10 Muaro Jambi. The research aims to identify the implementation of the Deep Learning model in Grade X Phase E7 and E8 and to analyze its influence on students’ creativity. This study employed a quantitative method with an experimental design. The population consisted of 235 students, with a sample of 63 students selected through purposive sampling, including 30 students in the control class and 33 students in the experimental class. Data were collected through questionnaires, observations, and documentation using a Likert scale based on creativity indicators: fluency, flexibility, originality, and elaboration. Data analysis involved validity, reliability, normality, homogeneity, and hypothesis testing using the Independent Sample t-test with SPSS. The results indicate that the Deep Learning approach has a significant effect on students’ creativity, as evidenced by a significance value of 0.000 < 0.05 and a t-value of 7.352, leading to the rejection of H₀ and acceptance of H₁. Furthermore, the experimental class showed notable improvements across all creativity indicators, while the control class showed less significant changes. These findings confirm that the Deep Learning approach effectively enhances students’ creativity in Geography learning.